Gambaran Status Kebersihan Rongga Mulut dan Status Gingiva Pasien RSGM Universitas Jember Oktober-November Tahun 2015 (The Description of Oral Hygiene Status and Gingival Status of Patients in Dental Hospital of Jemb - Cici Widya Anggraini; Melok Aris Wahyukundari; Peni Pujiastuti (Pustaka Kesehatan, 2016)
Background : Oral hygiene is very important to be kept for aestetic, phonetic,mastication function and health. There is a relationship between oral hygiene andgingival desease. Poor oral hygiene will increase the severity of gingival disease.However, some people still consider that oral hygiene issue is not something important.Purpose : To find out the status of oral hygiene and gingival status of patients in DentalHospital of Jember University and reviewed by age, gender and education. Metode :This study was a descriptive study with cross sectional approach. The samples were allnew patients of Dental Hospital of Jember University on October-November 2015. Theoral hygiene status was assessed by Oral Hygiene Index-Simplified (OHI-S) and gingivalstatus was assessed by Gingival Index (GI). Result : There were 35,84% of sample hada good oral hygiene, 54,87% had a medium oral hygiene and 9,29% had a poor oralhygiene. There were 7,08% of sample had a normal gingival, 58,85% had a light gingivalinflamation, 33,63% had a moderate gingival inflamation, and 0,44% had a severegingival inflamation.Keywords : Gingivitis, GI, OHI-S, Oral hygiene